2018
DOI: 10.1186/s12711-018-0403-0
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian estimation of direct and correlated responses to selection on linear or ratio expressions of feed efficiency in pigs

Abstract: BackgroundThis study aimed at (1) deriving Bayesian methods to predict breeding values for ratio (i.e. feed conversion ratio; FCR) or linear (i.e. residual feed intake; RFI) traits; (2) estimating genetic parameters for average daily feed consumption (ADFI), average daily weight gain (ADG), lean meat percentage (LMP) along with the derived traits of RFI and FCR; and (3) deriving Bayesian estimates of direct and correlated responses to selection on RFI, FCR, ADG, ADFI, and LMP. Response to selection was defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 26 publications
2
41
1
Order By: Relevance
“…It is also possible that the prior of the Bayesian animal model overly influenced the estimate. In contrast to other studies that reported heritabilities of ADG and FCR in pigs ranging from 0.05 to 0.48 and 0.22 to 0.40 for ADG and FCR, respectively (Kavlak & Uimari, 2019; Nascimento, Nascimento, Dekkers, & Serão, 2019; Saintilan et al, 2013; Shirali, Varley, & Jensen, 2018; Silva, Lopes, Lopes, & Gasparino, 2019), our heritability estimate of ADG was close to zero and the one of FCR was rather low. Several QTLs were identified for ADG (Shirali et al, 2013; Silva et al, 2019) and FCR (Reyer et al, 2017; Silva et al, 2019), indicating a genetic basis of these traits.…”
Section: Discussioncontrasting
confidence: 61%
“…It is also possible that the prior of the Bayesian animal model overly influenced the estimate. In contrast to other studies that reported heritabilities of ADG and FCR in pigs ranging from 0.05 to 0.48 and 0.22 to 0.40 for ADG and FCR, respectively (Kavlak & Uimari, 2019; Nascimento, Nascimento, Dekkers, & Serão, 2019; Saintilan et al, 2013; Shirali, Varley, & Jensen, 2018; Silva, Lopes, Lopes, & Gasparino, 2019), our heritability estimate of ADG was close to zero and the one of FCR was rather low. Several QTLs were identified for ADG (Shirali et al, 2013; Silva et al, 2019) and FCR (Reyer et al, 2017; Silva et al, 2019), indicating a genetic basis of these traits.…”
Section: Discussioncontrasting
confidence: 61%
“…However, expected direct response would be lower than that of selection based on phenotypic regression (i.e., RFI). Implementation of this definition of FE has been performed using multiple‐trait models for individual records of FI (Shirali, Varley, & Jensen, ; Strathe et al, ). Only Shirali, Nielsen, Moller, and Jensen () used group records of FI to estimate genetic parameters of the classical definition of RFI using a single‐trait model with different (but correlated) genetic and permanent effects for each cage mate, which could be considered a different approach.…”
Section: Introductionmentioning
confidence: 99%
“…To further complicate things, fillet yield is a ratio trait, and ratios have long been recognized as difficult traits to improve, because of their non-normality and because a given change in the ratio may be the result of different changes in its component traits. The expected genetic gain from truncation selection on ratio traits is difficult to compute using selection index theory, particularly when the component traits are correlated and have different means (Shirali et al, 2018). This is the case for the component traits of fillet yield, fillet weight, and body weight, which are very highly phenotypically and genetically correlated (r P = 0.89-0.99, r G = 0.93-0.99, see Fraslin et al, 2018 for a review).…”
Section: Introductionmentioning
confidence: 99%